2011
DOI: 10.1186/1471-2164-12-s3-s22
|View full text |Cite
|
Sign up to set email alerts
|

A comparative structural bioinformatics analysis of inherited mutations in β-D-Mannosidase across multiple species reveals a genotype-phenotype correlation

Abstract: BackgroundLysosomal β-D-mannosidase is a glycosyl hydrolase that breaks down the glycosidic bonds at the non-reducing end of N-linked glycoproteins. Hence, it is a crucial enzyme in polysaccharide degradation pathway. Mutations in the MANBA gene that codes for lysosomal β-mannosidase, result in improper coding and malfunctioning of protein, leading to β-mannosidosis. Studying the location of mutations on the enzyme structure is a rational approach in order to understand the functional consequences of these mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…In general, the nature of the mutation as well as its proximity to the active site may determine the severity of the phenotype observed . Thus, nonsense mutations Y126X, W192X, W231X, V321X, and Y485X leading to large truncations in β‐mannosidase typically show severe phenotypes .…”
Section: Resultsmentioning
confidence: 99%
“…In general, the nature of the mutation as well as its proximity to the active site may determine the severity of the phenotype observed . Thus, nonsense mutations Y126X, W192X, W231X, V321X, and Y485X leading to large truncations in β‐mannosidase typically show severe phenotypes .…”
Section: Resultsmentioning
confidence: 99%
“…Patients with β-mannosidosis have a wide spectrum of neurological involvement, including intellectual disability, hearing loss, ataxia, and seizures. 13 Phenotypegenotype correlation analysis revealed that truncation mutations often cause severe phenotypes, whereas substitution mutations may show mild phenotypes (Supplementary Table S11 online). 13 This study extends the scope of β-mannosidosis to the autosomal-dominant inheritance of infantile nystagmus.…”
Section: Discussionmentioning
confidence: 99%
“…13 Phenotypegenotype correlation analysis revealed that truncation mutations often cause severe phenotypes, whereas substitution mutations may show mild phenotypes (Supplementary Table S11 online). 13 This study extends the scope of β-mannosidosis to the autosomal-dominant inheritance of infantile nystagmus. The heterozygous mutations in MANBA identified in this study may represent the least severe β-mannosidosis that is limited to the eye regulatory regions in brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Neuropathology in Salers calves showed hydrocephalus and myelin deficiency in the cerebral hemispheres, cerebellum, and brainstem.…”
Section: B-mannosidosis In Other Speciesmentioning
confidence: 99%